2010
DOI: 10.1097/olq.0b013e3181e71069
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Determinants of Eight High-Risk Human Papillomavirus Types in Homosexual Men, Heterosexual Men, and Women: A Population-Based Study in Amsterdam

Abstract: Prevalence of 8 hrHPV antibodies was high in the Amsterdam population, especially in MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Prevalence of antibodies against HPV-16, which is the most carcinogenic and therefore most important HPV type, was high compared to other studies among (mostly heterosexual) males (16,17,34,41), but comparable to data reported for MSM specifically (40,42). However, comparisons between HPV serology studies are hampered by major differences in characteristics of the study population and in serology methods.…”
Section: Discussionmentioning
confidence: 47%
“…Prevalence of antibodies against HPV-16, which is the most carcinogenic and therefore most important HPV type, was high compared to other studies among (mostly heterosexual) males (16,17,34,41), but comparable to data reported for MSM specifically (40,42). However, comparisons between HPV serology studies are hampered by major differences in characteristics of the study population and in serology methods.…”
Section: Discussionmentioning
confidence: 47%
“…More recent publications have highlighted the importance of age of sexual debut, [8] marital status, [29] high number of lifetime sexual partners, [5,30,31] number of recent sexual partners, [30] longer history of sexual activity, [30] route of exposure, [26,30,32] and having sex with men [32][33][34] as risk factors for anogenital HPV infection. Similar observations about sexual risk behaviour and an association with HPV have been made in studies of men in SSA.…”
Section: Factors Associated With Hpv Infectionmentioning
confidence: 99%
“…[17,36,38,39] Related findings from the trial in Kenya have highlighted less frequent bathing as a risk factor for HPV infection, which may be associated with poor genital hygiene in uncircumcised men. [18,28] STIs are independently associated with the risk of HPV infection, particularly chlamydia, [19,30] herpes simplex virus (HSV)-2, [34] and hepatitis B. [40] While they may share a common mode of transmission, STIs are thought to increase the risk of HPV infection by facilitating access to the basal epithelium through micro-abrasions in the skin.…”
Section: Factors Associated With Hpv Infectionmentioning
confidence: 99%
“…[12] The quadrivalent vaccine has demonstrated efficacy in the prevention of cervical, vulvar and vaginal cancer, genital warts and precancerous or dysplastic lesions caused by HPV types 6, 11, 16 and 18 in females, [10] and estimates show that, as well as being potentially cost effective, [13] national vaccination programmes targeting adolescent females and young women can be expected to result in decreased incidences of HPV infection [14] and genital warts, [15] in both females and heterosexual males (HM) as a result of herd immunity. [15] However, no change was predicted for men who have sex with men (MSM; a group with a high prevalence of HPV infection [16] ) or females outside the age range for vaccination. [15] Various arguments exist in favour of nationwide vaccination of males as well as females, including the increased likelihood of herd immunity, increased effect in the MSM population and decreased incidence of HPV-associated disease in males (potentially more so than is associated with decreased transmission of the virus from females).…”
Section: Most Common Adverse Events (≥5% Of Males Aged 9-26 Years Recmentioning
confidence: 99%
“…Features and properties of the quadrivalent human papillomavirus (HPV) types 6,11,16,18 vaccine (Gardasil®)…”
mentioning
confidence: 99%